Enhancer of zeste homolog 2 (EZH2) regulates tumor angiogenesis and predicts recurrence and prognosis of intrahepatic cholangiocarcinoma. Issue 10 (October 2018) - Nakagawa, Shigeki; Okabe, Hirohisa; Ouchi, Mayuko; Tokunaga, Ryuma; Umezaki, Naoki; Higashi, Takaaki; Kaida, Takatoshi; Arima, Kota; Kitano, Yuki; Kuroki, Hideyuki; Mima, Kosuke; Nitta, Hidetoshi; et al.
Abstract: Background: Enhancer of zeste homolog 2 (EZH2) is the catalytic subunit of the polycomb repressive complex 2 (PRC2) and regulates tumor malignancy by gene silencing via histone methylation. In this study we investigate the role of EZH2 in angiogenesis of intrahepatic cholangiocarcinoma (ICC). Methods: The influence of EZH2 on tumor angiogenesis was examined by bioinformatics analysis of a public database. We also assessed the correlation between EZH2 and vasohibin 1 (VASH1) expression in 47 patients with ICC by immunohistochemical (IHC) staining and in vitro gene silencing assays. The prognostic significance of EZH2 and VASH1 expression by IHC was also examined in the ICC cohort. Results: Bioinformatics analysis showed that EZH2 was associated with several angiogenesis gene sets in the public database. EZH2 suppressed VASH1 expression in in vitro assays and IHC studies. EZH2-high/VASH1-low status was independently associated with poor disease-free survival (P = 0.019) and poor overall survival (P = 0.0055). Conclusion: The current study demonstrated that high EZH2 expression was associated with activation of tumor angiogenesis, and activation of the EZH2-mediated angiogenesis pathway predicted the prognosis of patients with ICC.